Role of social support in self-management of health - Visvalingam A.; Dhillon J.S.; Gunasekaran S.S. (University of Tehran, 2023)
Social support is the physical and emotional comfort given to someone in times of need or crises and it is especially important for maintaining good physical and mental health. Despite the contribution of intelligent technological devices, which have led to the availability of various types of social support systems, the latter are still not widely known to many. These support systems are currently available in many versions, such as in tablets and smartphones, where many health information systems have been created specifically to accommodate to the needs of current mobile healthcare consumers. In this paper, we systematically review the role of social support provided via health information systems and report a qualitative study that investigates the perceptions of healthcare professionals and consumers towards incorporating social support in self-care applications. The results obtained through our study reveal that social support is associated with better health management and is a vital component to be incorporated in any novel health information system. Likewise, the results are supported by our qualitative study that indicates healthcare professionals and consumers emphasize the inclusion of the social support component in self-care applications to achieve better health outcomes. University of Tehran, Faculty of Management